A New Direction of Arabic Language Teaching: Integration of Muthala’ah Text Book and Religious Moderation Concept - Imron, Kristina; Abdullah, Muhammad Yahya; Nurani, Qoim; Rohayati, Enok; Jamanuddin, Jamanuddin (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This research aims to develop religious moderation-based Muthola’ah teaching materials in textbooks and test the effectiveness of the products developed empirically in class IX of the Izzatuna Islamic Boarding School (SMP) in Palembang. This research uses a research and development design with the Borg and Gall model, which initially contained ten development steps. However, due to limitations, this research was limited to six steps that were sufficient to answer the objectives. This research was designed based on the results of an analysis of the needs of teachers (77.03%) and students (78.50%) regarding religious moderation material to implement learning while still paying attention to the socio-cultural context of society. The results of this research are a Muthola’ah textbook based on religious moderation. Its effectiveness has been tested, so this product is suitable for Muthola’ah learning and has positive implications for increasing students' understanding of religious moderation.